151k views
1 vote
9(x-2) + 3(5-2x) = 2

2 Answers

3 votes
9x -18 + 15 -6x = 2
3x -3= 2
3x= 5
X= 5/3

Hope this helps!

User Jinnie
by
5.2k points
6 votes

First you must distribute the numbers outside the parentheses to the numbers inside the parentheses

Let's start with the first one:

9(x-2) + 3(5-2x) = 2

9(x - 2)

9*x + 9*-2

9x + (-18)

9x - 18

so...

9x - 18 + 3(5-2x) = 2

Now on to the second set of parentheses:

9x - 18 + 3(5-2x) = 2

3(5 - 2x)

3*5 + 3*-2x

15 + (-6x)

15 - 6x

so...

9x - 18 + 15 - 6x = 2

Now you must combine like terms. This means the numbers with the same variables must be combined...

First set of like terms:

9x - 18 + 15 - 6x = 2

9x + (-6x)

3x

so...

3x - 18 + 15 = 2

Second set of like terms:

3x - 18 + 15 = 2

-18 + 15

-3

so...

3x - 3 = 2

Now bring -3 to the right side by adding 3 to both sides (what you do on one side you must do to the other). Since -3 is being negative on the left side, addition (the opposite of negative/subtraction) will cancel it out (make it zero) from the left side and bring it over to the right side.

3x + (- 3 + 3) = 2 + 3

3x + 0 =5

3x = 5

Next divide 3 to both sides to finish isolating x. Since 3 is being multiplied by x, division (the opposite of multiplication) will cancel 3 out (in this case it will make 3 one) from the left side and bring it over to the right side.

3x/3 = 5/3

x =
(5)/(3)

Hope this helped!

~Just a girl in love with Shawn Mendes

User Karoberts
by
5.1k points